The Millennium Development Goals - thinking beyond the Sachs report - Dirk Messner; Peter Wolff (Deutsches Institut für Entwicklungspolitik (DIE), 2005)
The Sachs Report is innovative in that it develops strategies designed to dynamize the economies of the poorest developing countries with ”investments to empower poor people”. It develops and points to approaches for ”pro-poor growth” policies. Yet international development policy would be well advised to think beyond the Sachs Report: 1. To ensure that it is used effectively, ODA (Official Development Assistance) should rise successively, not jump sharply. 2. Rising ODA investments must be linked to clear-cut incentives and conditionalities designed to improve good governance in developing countries. 3. ODA should be increased substantially, starting with the world's 15-20 poorest countries with good governance, although this would make sense only if the donors subscribed, in this country group, to an approach based in large measure on a division of labor – the EU member states could provide a good example by taking the lead here. Germany should focus its engagement on roughly five of these developing countries. 4. The donors must work to ensure good governance in the bi- and multilateral development agencies. Clear-cut task profiles and a division of labor geared to advantages of specialization are among the conditions needed for coordination, effectiveness, and cost reduction in international development cooperation.
Keywords: 330